Phishing Websites Detection Using Machine Learning (International Journal of Advanced Research in Science, Management and Technology, 2023)
Phishing is a common attack on credulous people by making them to disclose their unique information using counterfeit websites Phishing website is one of the internet security problems that target the human vulnerabilities rather than software vulnerabilities. It can be described as the process of attracting online users to obtain their sensitive information such as usernames and passwords. In this paper, we offer an intelligent system for detecting phishing websites. The system acts as an additional functionality to an internet browser as an web page based extension that automatically notifies the user when it detects a phishing website. The system is based on a machine learning method, particularly supervised learning.
Keywords: Phishing, Phishing Websites, Detection, Machine Learning